2021
DOI: 10.3389/fphys.2021.645529
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation With Phytogenic Compounds Modulates Salivation and Salivary Physico-Chemical Composition in Cattle Fed a High-Concentrate Diet

Abstract: Saliva facilitates feed ingestion, nutrient circulation, and represents an important pH buffer for ruminants, especially for cattle fed high-concentrate diets that promote rumen acidification. This experiment evaluated the short-term effects of nine phytogenic compounds on salivation, saliva physico-chemical composition as well as ingested feed boli characteristics in cattle. A total of nine ruminally cannulated Holstein cows were used. Each compound was tested in four of these cows as part of a high-concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 61 publications
1
6
1
Order By: Relevance
“…This supports our findings showing that when the cows consumed the HG rations at a faster pace, the feed ensalivation was lower. With regard to the effect of phytogenic compounds on salivation, the increased salivation rate via individual phytogenic compounds previously reported [ 37 ] in a short-term trial was not confirmed in the present study. These contrasting findings may be because the stimulus for the salivation flow of individual phytogenic compounds could decrease when combined with other compounds.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This supports our findings showing that when the cows consumed the HG rations at a faster pace, the feed ensalivation was lower. With regard to the effect of phytogenic compounds on salivation, the increased salivation rate via individual phytogenic compounds previously reported [ 37 ] in a short-term trial was not confirmed in the present study. These contrasting findings may be because the stimulus for the salivation flow of individual phytogenic compounds could decrease when combined with other compounds.…”
Section: Discussioncontrasting
confidence: 99%
“…Saliva samples were collected orally once a week ( Figure 1 ) to evaluate salivary physico-chemical characteristics, with the first collection conducted in week 0, and the following collections performed in each of the 4 weeks of the HG feeding regimen. Details of saliva samplings have been described by Castillo-Lopez et al [ 28 ] and Ricci et al [ 37 ]. Briefly, saliva collections were conducted with a vacuum pump before the morning feeding.…”
Section: Methodsmentioning
confidence: 99%
“…No effects on fermentation parameters or pH were found, which was unexpected. A positive influence of capsaicin on chewing activity during feeding of high‐concentrate diets has been previously reported by our team (Ricci et al, 2021). As artificial saliva was kept at a constant flow rate in our study, it is very likely that the effect of capsaicin in salivary dynamics was neglected.…”
Section: Discussionsupporting
confidence: 81%
“…In order to maintain healthy rumen function, ruminants require dietary fiber and its consumption triggers chewing, saliva production and rumination, which are important for proper digestion. Saliva contains sodium bicarbonate and phosphate salts (Humphrey and Williamson, 2001) which facilitates feed ingestion, and nutrient circulation, and represent an important pH buffer for ruminants, especially for cattle fed highconcentrate diets that promote rumen acidification (Ricci et al, 2021). In the current study, both bamboo leaves and the grasses were fibrous, thus, can enhance chewing and stimulate saliva to maintain the rumen pH required to prevent metabolic disorders in ruminants fed high-grain diets.…”
Section: Discussionmentioning
confidence: 77%